Evaluation of response after pre-operative radiotherapy in soft tissue sarcomas; the European Organisation for Research and Treatment of Cancer - Soft Tissue and Bone Sarcoma Group (EORTC - STBSG) and Imaging Group recommendations for radiological examination and reporting with an emphasis on magnetic resonance imaging - Messiou, Christina; Meyer, Mathias (European journal of cancer, 2016)
At present, there is no standardised approach for the radiological evaluation of soft tissue sarcomas following radiotherapy (RT). This manuscript, produced by a European Organisation for Research and Treatment of Cancer - Soft Tissue and Bone Sarcoma Group (EORTC - STBSG) and Imaging Group endorsed task force, aims to propose standardisation of magnetic resonance imaging techniques and interpretation after neoadjuvant RT for routine use and within clinical trials.
Gesehen am 23.05.2019